Étude des compétences propices au soin et à la transformation de l’environnement - Diane Pruneau; Jackie Kerry; Joanne Langis (VertigO)
In a world in which the environment is strained and humans are confronted to environmental diseases, which competencies (ways of thinking) allow some citizens to transform their communities ? The goal of the multiple cases study was to identify multidisciplinary competencies demonstrated by two groups of citizens involved in sustainable development : farmers adapting to climate change and leaders creating an exemplary sustainable neighbourhood. Competencies used by the actors of these two projects, studied using participatory observation, interviews and document analysis, were creative problem solving, technical and indigenous knowledge, collaboration, critical thinking, optimism, perseverance, openness to novelty and learning interest. Planning is a competency mostly used by the sustainable neighbourhood builders. A discussion invites the reader to reflect on the possibility of developing students’ environmental competencies while helping them reason while considering community identity, viability and vitality.